PENINGKATAN KOMPETENSI GURU DALAM MERANCANG ASSESSMENT OF LEARNING YANG BERKUALITAS UNTUK MENGUKUR HASIL BELAJAR SECARA OPTIMAL - Rosmiati; Wahyu Susiloningsih; Susi Hermin Rusminati; Triman Juniarso; Apri Irianto (Kanigara, 2025)
Asessment of learning outcomes is a crucial component of the educational process, with Assessment of Learning (AoL) serving as a key approach to evaluating students' achievements after the learning process. However, many teachers face challenges in designing valid, reliable, and appropriate assessment instruments that meet learning needs. This study aims to enhance teachers' competencies in designing high-quality AoL through an intensive training program. The methodology involves needs analysis, training material development, workshops, group discussions, practical simulations, as well as mentoring and field supervision. The training results show a significant improvement in teachers' understanding of concepts such as validity, reliability, and their ability to develop instruments based on Higher Order Thinking Skills (HOTS). The increase in the average score from the pre-test to the post-test by 24.7% demonstrates the program's success in improving teachers' competencies. This study highlights the importance of an integrated training approach to optimize teachers' abilities in designing high-quality assessments that support educational success.